Fish Index for Classifying Riverine Ecosystem of Peninsular Malaysia - Ismail M, Zakaria; A, Fatimah (Malaysian Journal of Science, 2002)
Tolerance levels of common freshwater fishes found in the various freshwater ecosystems of Peninsular Malaysia are presented to enable calculation of the fish index (FI) in the field for river classification purpose. These tolerance levels range from 0.5 to 4.5. Smaller values are for sensitive fishes that cannot tolerate even a small change in the surrounding environment, while larger values are for fishes that can withstand a wide range of environmental changes. From the study, Channa gachua (family Channidae), Clarias teijsmanni (family Clariidae), Glyptothorax major and Glyptothorax platypogonoides (both from family Sisoridae) are considered to be the most sensitive species with tolerance value of 1 or smaller. On the other hand, Liposarcus pardalis (family Loricariidae) is the most tolerant fish with a tolerance level of 4.5. This species is the dominant fish in the heavily polluted riverine ecosystem. The present river classification based on fish index is similar with the river classification system based on water quality index (WQI) widely used by the Department of Environment, Malaysia. However, the FI is a much easier and cheaper index to use as compared to WQI in the classification of rivers in Peninsular Malaysia.